Accidental overdose in the deep shade of night: a warning on the assumed safety of 'natural substances'. (5th November 2015) - Chadwick, Andrew; Ash, Abigail; Day, James; Borthwick, Mark
Abstract : There is an increasing use of herbal remedies and medicines, with a commonly held belief that natural substances are safe. We present the case of a 50-year-old woman who was a trained herbalist and had purchased an ' Atropa belladonna (deadly nightshade) preparation'. Attempting to combat her insomnia, late one evening she deliberately ingested a small portion of this, approximately 50 mL. Unintentionally, this was equivalent to a very large (15 mg) dose of atropine and she presented in an acute anticholinergic syndrome (confused, tachycardic and hypertensive) to our accident and emergency department. She received supportive management in our intensive treatment unit including mechanical ventilation. Fortunately, there were no long-term sequelae from this episode. However, this dramatic clinical presentation does highlight the potential dangers posed by herbal remedies. Furthermore, this case provides clinicians with an important insight into potentially dangerous products available legally within the UK. To help clinicians' understanding of this our discussion explains the manufacture and 'dosing' of the A. belladonna preparation.